1994
DOI: 10.1128/iai.62.1.48-59.1994
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an iron-regulated hemopexin receptor in Haemophilus influenzae type b

Abstract: Heme can serve Haemophilus influenzae as a source of both essential porphyrin and iron. In extracellular mammalian body fluids neither free heme nor free iron is available, since they are tightly bound to hemopexin and transferrin, respectively. Since H. influenzae grows in the presence of iron-transferrin and heme-hemopexin and is known to express a saturable receptor for transferrin, we investigated the process by which this pathogen acquired heme from hemopexin for use as an iron source. The ability of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…Furthermore, the HxuA-haemopexin complex lacks the high affinity for haem of haemopexin alone, and our experiments set an upper limit for the potential affinity of the HxuAhaemopexin complex for haem (below 10 6 M -1 , much lower than that of human serum albumin). HxuA interacts very strongly with haemopexin, as shown in previous studies (Wong et al, 1994;, and we have shown that HxuA forms high-affinity stoichiometric complexes with both apo-and haem-haemopexin. As the haem environment is modified by the formation of a complex between HxuA and haem-haemopexin, the affinity constant determined by ITC for this interaction is only apparent, as it takes into account both the protein-protein interaction and the change in haem environment.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the HxuA-haemopexin complex lacks the high affinity for haem of haemopexin alone, and our experiments set an upper limit for the potential affinity of the HxuAhaemopexin complex for haem (below 10 6 M -1 , much lower than that of human serum albumin). HxuA interacts very strongly with haemopexin, as shown in previous studies (Wong et al, 1994;, and we have shown that HxuA forms high-affinity stoichiometric complexes with both apo-and haem-haemopexin. As the haem environment is modified by the formation of a complex between HxuA and haem-haemopexin, the affinity constant determined by ITC for this interaction is only apparent, as it takes into account both the protein-protein interaction and the change in haem environment.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have identi¢ed an additional heme: hemopexin binding complex that is regulated by ambient levels of iron [167]. In this complex, the receptor is a 57-kDa protein that is anchored in the outer membrane.…”
Section: Iron and Heme Acquisitionmentioning
confidence: 99%
“…Recent studies have identified an additional heme:hemopexin binding complex that is regulated by ambient levels of iron [167]. In this complex, the receptor is a 57‐kDa protein that is anchored in the outer membrane.…”
Section: Persistencementioning
confidence: 99%